Analysis of Temporal and Spatial Variation of Tidal Wave Characteristics in Macao under the Influence of Reclamation - WANG Renchao; ZHANG Gongjin (Renmin Zhujiang)
With the historical tidal level data,this paper analyzes the temporal and spatial variation characteristics of tidal constituents and the influence of reclamation intensity on tidal level variation in the Macao sea area over the years.The results indicate that the waters near the Macao station show irregular semidiurnal tides,and the tidal wave deformation is significant over the years and fluctuates in different periods.The value of HS2/HM2 at the Macao station fluctuates around 0.4 over the years,which reflects that the diurnal variation of tide height at the Macao station is significantly influenced by time.The empirical orthogonal function (EOF) method is used to discuss the long-series tidal level change at the Macao station.The variance contribution rate of the first characteristic vector is 79%,and it is a typical combination of tidal constituent amplitudes.According to the correlation analysis between the first characteristic vector and the reclamation strength of the Macao sea area,the correlation coefficient is 84%,which manifests that the reclamation project of Macao is the main influencing factor leading to the tidal wave deformation of the Macao sea area.